The Perfect Surgical Assistant: Calm, Confident, Competent and Courageous. Issue 9 (September 2016) - Hall, S; Quick, J; Hall, AW
Poor surgical assistance has been identified as a major stressor in surgeons, making the ability to provide effective surgical assistance an important skill which will have a lifelong impact on the surgical patient. Knowledge and technical ability are clearly important, but strong personal qualities are more so in the long run. This applies to all who provide assistance either as a surgical first assistant or surgical care practitioner. These skills and attributes are needed to provide a safe service that meets the expectations of both the professional regulatory authorities and surgical Royal Colleges. Advice is given in this article as to how non-medical practitioners may acquire these skills.